Serum C-reactive Protein Predicts Early Mortality in Patients with Decompensated Cirrhosis of Liver (Bangladesh Medical Journal, 2021)
Serum C-reactive protein is a marker of systemic inflammation, which has been studied to predict mortality and cirrhosis related complication in decompensated cirrhosis  of liver. To evaluate the role of serum C- reactive protein as a predictor of early mortality in patients with decompensated cirrhosis of liver. This was a prospective observational study, carried out in the Department of Hepatology, Bangabandhu Sheikh Mujib Medical University, Dhaka between October 2017 to February 2019. A total of 89 patients with decompensated cirrhosis of liver  were included in the study. Baseline serum CRP was measured and patients were longitudinally followed for a period of 30 days. Patients were divided into two groups, survival and non-survival. The groups were compared of CRP level, CTP score, MELD score and cirrhosis related complications. Chi-Square test was used to analyze the categorical variables and Student t-test was used to analyze continuous variables. Receiver-operator characteristic curve was used to detect serum CRP level for prediction of mortality within 30 days. The mean age was found 49.02±13.90 years in survival group and 47.52±11.30 years in non-survival group. Male patients were predominant in both groups. Total WBC count, serum CRP, serum sodium, serum  bilirubin, CTP score & MELD score were statistically significant (p